MEMBRANE PROCEDURES IN COMMUNAL WASTE LANDFILL LEACHATE TREATMENT - Nebojša Knežević; Siniša Cukut; Saša Dunović (Journal of Engineering & Processing Management, 2012)
One of basic problems faced in practice of landfill waste treatment is a problem with landfill leachate. The intensity of their production, thus their quantity, depends on numerous factors: landfill age, waste types, microclimatic parameters and similar. This leachate must not be discharge directly into the environment without their previous collection and treatment. The water found in solid waste, as well as waters that infiltrate into the landfill form a medium that dissolves all soluble substances and causes the unreacted material move downwards, towards the landfill bottom. This water is known as leachate. Leachate chemical properties are influenced by biological disintegration of biodegradable organic matter, chemical oxidation processes and disintegration of organic and non-organic matters found in waste.
Keywords: municipal waste; MW landfill; leachate; treatment; membrane’s processes